Overcoming the anxiety of speaking Arabic as a foreign language from students' perspectives: a qualitative case study - Abou El-Goukh, Sarah (AUC Knowledge Fountain, 2014)
This exploratory study was designed to investigate the role of students' perceptions on decreasing speaking anxiety within the Arabic as a foreign language classroom in the target language country. Qualitative methods were used in the research project. Qualitative instruments included: pre and post questionnaires, pre and post semi-structured interviews, and observation. Seven participants took part in the study; they were studying Modern Standard Arabic in an intensive program in Morocco. The results showed that students' perceptions and their suggestions had an impact on the learning process of the students and the importance to take into consideration students suggestions and to implement them within the classroom. The implications of the study include that (1) developing the proficiency of the students plays an important role in decreasing speaking anxiety; (2) the teacher's attitude has an impact on the process of learning and the classroom atmosphere; (3) providing students with speaking activities related to real life situations is an effective strategy to provoke student involvement and finally (4) the kind of teachers' feedback is an important factor for motivation and overcoming anxiety in the FL classroom.